THE EFFECT OF MOTIVATION, PARENTS’ ATTENTION, AND INTEREST IN LEARNING OUTCOMES ON DISTANCE LEARNING - Ningsih, Mulyati; Suroyo; Tatminingsih, Sri (AULADUNA: Jurnal Pendidikan Dasar Islam, 2022)
Abstract The purpose of conducting this research was to examine the influence of learning motivation and interest of students and parents’ attention on learning outcomes during distance learning. This research used quantitative method with a correlational approach. The population was all students of the fourth, fifth, and sixth grades in SDN 117 Pekanbaru, while the sample was 128 students selected using probability sampling. The instrument was a questionnaire by giving a series of questions to students. The data were analyzed using statistical data analysis with multiple regression. The results indicated a clear partial or simultaneous relevance of learning motivation, parental attention, and interest in learning to student learning outcomes. Therefore, teachers need to increase students’ motivation and interest in learning at school and establish communication with parents to increase their attention to their children.